Identification of a novel factor X deletion in combination with a missense mutation in the F10 gene - Hainmann, I.; Oldenburg, J.; Pavlova, A.; Superti-Furga, A.; Zieger, B. (Hämostaseologie, 2009)
The genotype-phenotype relationship of compound heterozygous factor X deficiency in a young girl with severe factor X deficiency and bleeding symptoms is characterized. We identified a novel deletion of exon 6 and a missense mutation (c.856G>A, Val286Met) in exon 7 of the F10 gene leading to a compound heterozygous state and causing severe factor X deficiency. Therapeutic options for patients with symptomatic factor X deficiency are demonstrated.
Keywords: Factor X deficiency; compound heterozygous mutation; deletion; missense mutation